In Vitro α-Glucosidase Inhibition and Antioxidant Activity of Mulberry (Morus Alba L.) Leaf Ethanolic Extract - Danuri, Hasim Muhamad; Lestari, Widia Ayu; Sugiman, Uci; Faridah, Didah Nur (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This present work aimed to investigate the in vitro antioxidant activity and α-glucosidase inhibitory effect of mulberry leaf ethanolic extract. Antioxidant analysis was performed using Thiobarbituric Acid (TBA) assay at concentrations of 125, 200, 500, and 1,000 ppm. The results showed that the optimum incubation time was four days and the extracts could reduce the formation of MDA, i.e. 41.21%, 45.33%, 44.19%, and 36.00%, respectively. This suggests that concentration of 200 ppm was found as the best treatment. In addition, the result showed that ethanolic extract of mulberry leaf also showed inhibition against α-glucosidase with the IC50 of 309.82 µg/ml.